The life of Courage the notorious thief, whore, and vagabond - Grimmelshausen, Hans Jakob Christoph von 1625-1676; Mitchell, Mike (Sawtry, Cambs Dedalus, 2001)
"A young girl caught up in the turmoil of the Thirty Years War, she survives, even prospers, by the use of her native cunning and sexual attraction. Completely amoral, she flits from man to man, having a succession of husbands and lovers, and ends her life with a band of gypsies."--Back cover.
KAL-3483, donated by Prof. Thomas David F. Chavez.
Keywords: Thirty Years' War, 1618-1648 -- Fiction